(3eLehY aj GdcjejGAs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3heeG hLO ai HYV eUGMa GdTGejjf HSe Gddg GdCMO GdUeO hgPG eHJOC cdGei ai UOQ gPG GdeUMa HYhf Gddg hJhajbg Efi CQOJ Cf jUd Edi cdGei gPG ef HYOi s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg (B: (3ajfHZi def Sdc gPG GdSHjd Cf jYQa ebGOjQ gPG GdfjQGf hceG HZOh GdQMe GdfWaI aEf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs